Rural youth and schooling: from denial of rights to possibilities of resistance in Chapada do Apodi-Ceará (Research, Society and Development, 2020)
Rural youth is the focus of this study, with spatial focus on young people from communities located in Chapada do Apodi, especially in the municipalities of Limoeiro do Norte and Quixeré. The research aimed to analyze the challenges of schooling the youth of Chapada do Apodi, in the aspects of access and permanence, as well as to discuss the possibilities of resistance that are built in Chapada do Apodi. The study was divided into two moments: the first discusses the categories territory, rural education and rural youth, articulating them to the context in focus. The second part deals with field research, in which young people from Chapada do Apodi, enrolled or not in high school, were interviewed. The research made it possible to learn about their schooling trajectories, marked sometimes by discontinuity, sometimes by staying in school, allowing to reflect that the context denies this right to several subjects. However, resistance experiences are gradually built in Chapada, which stimulate the redesign of this scenario. Finally, we consider the Jaguaribana Agricultural Family School Zé Maria do Tomé, focused on the formation of rural youth in the region, as an experience that illustrates the political-educational praxis that arises from the resistance of individuals, movements and social collectives.